Decolonising humanitarian health: A scoping review of practical guidance. - Amber Clarke; Katharina Richter; Michelle Lokot; Althea-Maria Rivas; Sali Hafez; Neha S Singh (PLOS Global Public Health)
Despite growing calls and efforts to decolonise global and humanitarian health, there is limited practical guidance for researchers, educators and practitioners on how to do so. This paper fills this gap by offering a narrative exploration of key recommendations on decolonising global/humanitarian health research, partnerships, teaching, organisational structures and other practices. We present concrete guidelines to support humanitarian actors in decolonising their work. We used a scoping review method. The search strategy was built on three overarching themes: decolonising, global health/health and humanitarian crises. We combined a MEDLINE and Web of Science database search with a grey literature search. In total, we screened abstracts and titles of 533 documents, excluding records that did not specifically refer to 'decolonising,' humanitarian and/or global health. We assessed full texts of 58 documents for eligibility, excluding documents that did not include practical recommendations. In total, 15 documents were included in this review. We identified five key themes: organisational structure, strategy and engagement; research partnerships and conceptualisations; funding for research and projects; the research lifecycle; and teaching and the curriculum. The principal finding is that humanitarian actors can decolonise their work by decentralising power, redistributing resources, critically reflecting on their work in the context of the broader socio-political landscape and recovering, centring and valuing marginalised Global South perspectives. Race was not a central analytical category in the reviewed literature, despite being an integral part of historical background narratives. Future research should reflect on practical steps towards racial justice in global/humanitarian health and be focused on ensuring that efforts towards "localisation" or "equitable partnerships" in global health are linked to decolonisation efforts, including in humanitarian health research. Our review underscores the importance of drawing on knowledge created by and for actors based in the Global South.